Application of small self-propelled drill rigs - Simić Nikola; Milanović Stefan; Kričak Lazar; Negovanović Milanka; Đokić Nikola (Podzemni Radovi)
Small-diameter drilling is used in many civil and mining engineering applications. In the past, it was mainly performed with hand-held hammer drills. However, the need for safer and more efficient work has led to the development of small self-propelled drilling machines that require fewer workers to achieve the same output while providing significantly safer working conditions. Small-diameter boreholes are used in specialized blasting methods (e.g., blasting in urban areas, secondary Boulder blasting), during the extraction of decorative stone blocks, for installing anchors in slope stabilization, in underground mining, in the application of expansive mortar for the disintegration of solid masses (stone, concrete), for creating protective screens, tunneling, and more. Several manufacturers produce small self-propelled drill rigs, all equipped with remote controls. This eliminates the need for the operator to stand in potentially hazardous positions, as is required when using hand-held hammer drills. This paper presents the capabilities and application methods of these drill machines under various working conditions.